2016
DOI: 10.1177/107327481602300417
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Case Series Report of Acinar Cell Carcinoma of the Pancreas

Abstract: Multidisciplinary treatment for acinar cell carcinoma of the pancreas should be considered due to the rarity of the disease and its lack of high-level therapeutic data. Progress in the molecular analysis of this tumor may improve outcomes through the use of personalized therapy based on underlying tumor mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 44 publications
(124 reference statements)
0
30
0
Order By: Relevance
“…Characteristics of ACC has been well understood by some systemic review worldwide and the effectiveness of preoperative diagnosis and surgical treatments were clarified at this stage [ [7] , [8] , [9] ]. ACC patients may have non-specific symptoms or laboratory data [ 10 ], and the present case had a discomfort at the site of mass lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of ACC has been well understood by some systemic review worldwide and the effectiveness of preoperative diagnosis and surgical treatments were clarified at this stage [ [7] , [8] , [9] ]. ACC patients may have non-specific symptoms or laboratory data [ 10 ], and the present case had a discomfort at the site of mass lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Curative pancreatectomy could be performed less than half of all ACC patients [ [3] , [7] ] and curability and tumor stage were influenced to patient prognosis although the tumor recurrence rate was still high [ 18 ]. In the present case, the problematic issue regarding operation was influences of prior operation and reconstruction procedure and we attempted to avoid injury of jejunal loop and its mesenteric vascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For metastatic PACC, the chemotherapy protocol of PDAC has been used, which includes gemcitabine, 5-FU, oxaliplatin, CPT-11, and S-1, or their combinations [ 14 16 ]. A systematic review by Glazer et al demonstrated that the disease control rate of chemotherapy was 55% and median survival time in metastatic PACC after chemotherapy was 17 months [ 17 ]. However, the efficacies of various chemotherapies have not been studied in controlled, prospective studies, and there are no definitive guidelines for the treatment of metastatic PACC.…”
Section: Discussionmentioning
confidence: 99%
“…The best therapeutic regimen is comprehensive treatment based on radical resection [ 14 ]. Patients with resectable lesion can benefit from surgical removal.…”
Section: Discussionmentioning
confidence: 99%